Sensorimotor coordination and time movement anticipation ability of badminton players and footballers - An analysis - Pandey, V.; Dureha, D.; Acharya, J. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
This study investigated and compared the sensorimotor coordination and time movement ability for badminton players and footballers. The objective of this study was to understand the psychological construct of the selected sport group for which 100 male sportspersons (50 each in badminton and football) in the age group 18-25 years with a mean & SD of 20.05 ± 2.04 were randomly selected. It is hypothesized that (i) no difference would be seen between both the groups in sensorimotor coordination;(ii) badminton players time movement anticipation would be faster than footballers.For measuring sensorimotor coordination and time movement anticipation,Vienna test system (VTS), a computerized psychological assessment tool was used. Independent `t` test was applied at 0.05 level of significance . The results revealed that there is statistically significant difference in the mean deviation time medium fast (MDTMF), between badminton players and footballers as the obtained `t` value of 2.02 is greater than the required value of 1.98 at 98df. No statistically significant difference was observed in any other parameter; however the mean score of badminton players were better in comparison to footballers in the selected parameter. These results suggest that the badminton players have faster time movement anticipation as hypothesized. This may be owing to the nature of the sport.